Nucleofugal behavior of a β-shielded α-cyanovinyl carbanion - Knorr, Rudolf; Schmidt, Barbara (Beilstein Journal of Organic Chemistry, 2018)
Sterically well-shielded against unsolicited Michael addition and polymerization reactions, α-metalated α-(1,1,3,3-tetramethylindan-2-ylidene)acetonitriles added reversibly to three small aldehydes and two bulky ketones at room temperature. Experimental conditions were determined for transfer of the nucleofugal title carbanion unit between different carbonyl compounds. These readily occurring retro-additions via C–C(O) bond fission may also be used to generate different metal derivatives of the nucleofugal anions as equilibrium components. Fluoride-catalyzed, metal-free desilylation admitted carbonyl addition but blocked the retro-addition.
Keywords: alkoxide fission; desilylation; fragmentation; retro-addition; reversible carbonyl addition; shielded acrylonitrile